Age before acuity: the drivers of demand for emergency department services in the Greater Sydney Area. Issue 9 (18th December 2014) - Dinh, Michael M; Bein, Kendall J; Latt, Mark; Chalkley, Dane; Muscatello, David
Abstract : Objective: To contrast long-term population-based trends in general practice (GP) presentations and acute inpatient admissions from the emergency department (ED) in the elderly population within the Greater Sydney Area. Methods: This was a retrospective analysis of population-based ED presentation data over 11 years, between January 2001 and December 2011, conducted within the Greater Sydney Area in Australia. De-identified data were obtained from the New South Wales Emergency Department Data Collection database on all patients presenting to 30 public hospital EDs located within the Greater Sydney Area. The outcomes of interest were GP presentations to ED (triage category 4 or 5, self-referred and discharged from ED) and of acute inpatient admissions from ED per 1000 population. Results: Over 11 million presentations were identified. Around 40% of presentations were classified as a GP presentation and 23% were classified as acute inpatient admissions. There was a 2.9% per annum increase in acute inpatient admissions per 1000 population in those ≥80 years of age and no appreciable change in other age groups. Rates of GP presentations were higher in those <65 years of age. GP presentations increased 1.9% per annum in those aged <65 years of age. Conclusions: The increase in ED demand appears to be driven by the elderly presenting with acute problems requiring inpatient admission. There has been a modest increase in the rate of GP presentations to ED.